Генезис вугільних газів з відкладів карбону території шахти ім. А.Ф. Засядька (Донбас) - Ємець, О.В.; Лугова, І.П.; Канін, В.О.; Таранік, О.О.; Мороз, В.С. (Видавничий дім "Академперіодика" НАН України, 2008)
The paper provides information on the investigations of carbon isotopic ratios in coal, chemical content, and carbon isotopic characteristics of carbon dioxide and methane in coalbed gases of the Carboniferous beds of the A. F. Zasyadko coal mine (Donbas). It is established that the coalbed gases originated from kerogen-3 due to its thermal degradation. Extrinsic methane and carbon dioxide in some coalbed gases were detected. Probably, they were migrated from deeper levels of the Donets coal basin and (or) an endogenic source.